2009
DOI: 10.1002/bit.22391
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of coenzyme specificity of 2,3‐butanediol dehydrogenase from Saccharomyces cerevisae and in vivo functional analysis

Abstract: Saccharomyces cerevisiae NAD(H)-dependent 2,3-butanediol dehydrogenase (Bdh1), a medium chain dehydrogenase/reductase is the main enzyme catalyzing the reduction of acetoin to 2,3-butanediol. In this work we focused on altering the coenzyme specificity of Bdh1 from NAD(H) to NADP(H). Based on homology studies and the crystal structure of the NADP(H)-dependent yeast alcohol dehydrogenase Adh6, three adjacent residues (Glu(221), Ile(222), and Ala(223)) were predicted to be involved in the coenzyme specificity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 39 publications
1
33
0
Order By: Relevance
“…Overall, any modification of the balance between the oxidized and reduced forms of redox cofactors is expected to have far-reaching effects on the functional metabolic network. In agreement with this finding, altered metabolite patterns were identified in previous studies that focused on the impact of redox perturbations on fermentation kinetics and the formation of products from central carbon metabolism, such as glycerol, acetate, and succinate (19)(20)(21)(22)(23)(24).…”
supporting
confidence: 82%
See 2 more Smart Citations
“…Overall, any modification of the balance between the oxidized and reduced forms of redox cofactors is expected to have far-reaching effects on the functional metabolic network. In agreement with this finding, altered metabolite patterns were identified in previous studies that focused on the impact of redox perturbations on fermentation kinetics and the formation of products from central carbon metabolism, such as glycerol, acetate, and succinate (19)(20)(21)(22)(23)(24).…”
supporting
confidence: 82%
“…The strains used in this study were constructed from S. cerevisiae strain 59A, a haploid derivative of the wine yeast strain Lalvin EC1118 (29). The 59A-NADH-Bdh and 59A-NADPH-Bdh strains were obtained previously by overexpressing the BDH1 gene encoding the NADH-dependent 2,3-butanediol dehydrogenase (Bdh1p) or a mutated version of this gene encoding a NADPH-dependent Bdh1p (21,30). The S. cerevisiae strains were grown in yeast extract-peptone-dextrose (YPD) medium (1% Bacto yeast extract, 2% Bacto peptone, and 2% glucose).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the decreased acetoin accumulation, the most obvious effect of BDH1 or mutated BDH1 overexpression was decreased diacetyl production. Five enzymes having in vitro diacetyl reductase activity in S. cerevisiae, including Bdh1, which reduces diacetyl as the second best substrate after acetoin, have been identified previously (9,12,24,38,43). We have shown that the overexpression or deletion of BDH1 results in a twofold decrease or increase in diacetyl levels, respectively, suggesting that Bdh1 is a rate-limiting enzyme in diacetyl reduction.…”
Section: Discussionmentioning
confidence: 73%
“…An engineered NADPH-dependent Bdh1 enzyme was obtained by substituting 3 amino acids of the cofactor binding site (Ehsani et al, 2009b). Overproduction of the native and mutated enzymes in glycerol-overproducing strains showed that the availabilities of Bdh1 and NADH limited the BDH reaction, with the major rate-controlling factor being the amount of Bdh1 enzyme (Ehsani et al, 2009a). These strategies made it possible to redirect 85-90% of the accumulated acetoin to 2,3-butanediol.…”
Section: Glycerol Overproductionmentioning
confidence: 99%